TRANSFORMASI PENDIDIKAN AGAMA KRISTEN SEPANJANG SEJARAH GEREJA-GEREJA - Stefany Yosephine Edrika; Elizama Gulo (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Christian religious education has undergone significant transformations throughout church history. From the apostolic era to the modern age, Christian religious education has evolved and adapted to social, cultural, and theological changes. This article will examine the transformation of Christian religious education throughout church history, focusing on changes in the goals, methods, and content of Christian religious education. The transformation of Christian Religious Education (PAK) is a historical and theological process that takes place along with the church's journey in responding to the social, political, and cultural contexts throughout the ages. This study aims to trace significant changes in PAK from the Early Church era to the contemporary era. With a qualitative, historical, and theological approach, this study explores the dynamics of Christian faith education through a review of primary and secondary literature, as well as an analysis of church history documents. Each period in church history brings different educational models and approaches. The Early Church emphasized oral tradition and living communities, the Middle Ages emphasized church authority and clerical education, the Reformation opened access to Scripture and general literacy, while the modern and contemporary eras face the challenges of secularization and digitalization. From this journey, it can be seen that relevant PAK is one that is rooted in the Gospel and at the same time responsive to changes in the times.  As stated by Dr. Jan S. Aritonang, "Church history is a reflection of how believers struggle to shape spiritual life, including in faith education in the midst of a changing world." Therefore, this study aims to Research Objectives, Analyze the development of PAK from the early church era to the modern church. Identifying internal and external factors that influence the transformation of PAK. Developing practical implications for the development of contemporary PAK based on church history.